SKRINING DAN UJI DAYA HAMBAT ACTINOMYCETES DARI RIZOSFER TANAMAN KOPI ARABIKA DI KABUPATEN BENER MERIAH TERHADAP Collecotrichum coffeanum - Yusnizar Yusnizar; Fikrinda Fikrinda; Syafruddin Syafruddin; Hifnalisa Hifnalisa; Khairini Simahtuah (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
Actinomycetes are microorganisms of a group of gram-positive bacteria that produce uniseluser mycelium. Â Colonies of Actinomycetes grow slowly, are attached to the substrate and can produce spores. Actinomycetes are known to be able to control plant pathogens. This study aims to screen and study the inhibitory power of Actinomycetes from the rhizosphere of Arabica coffee rhizosphere against Collecotrichum coffeanum. This study found Actinomycetes in the rhizosphere of Arabika coffee plants from Bener Meriah. There were 80 Actinomycetes isolates. Eight of the 21 isolates selected isolate were against Collecotrichum coffeanum with different inhibitory ratios from each isolate. There were 1PRG/RR/10-3/2-1, 2PRG/WP/10-4/1-1-1, 2PRG/AG/10-4/3-1-1, 1M/SR/10-3/2-1, 2M/SR/10-3/2-1, 1M/JAJ/10-3/2-1, 1B//KR/10-3/2, 2B/KR/10-4/1.